Repurposing antimalarial artesunate for the prophylactic treatment of depression: Evidence from preclinical research. Issue 1 (27th December 2022) - Huang, Shihao; Galaj, Ewa; Wang, Jinfeng; Guo, Yi; Wang, Shuang; Shi, Mengxu; Yin, Xueyong; Liu, Keyao; Luo, Yixiao; Meng, Li; Shi, Haishui
Abstract: Introduction: Several studies have linked inflammation and oxidative stress with the pathogenesis of depression. Artesunate is a commonly used medication to treat malaria and has been shown to produce antioxidant, anti‐inflammatory, and immunomodulatory effects. However, its prophylactic effects on depression and depression‐related brain pathology are unknown. Methods: In Experiment 1, using a PC12 cell line, we investigated whether artesunate can prevent hydrogen peroxide (H2 O2 )‐induced oxidative injury that mimics oxidative stress commonly observed in the depressed brain. Next, using lipopolysaccharide (LPS)‐induced mouse model of depression, we investigated whether artesunate can prevent behavioral deficits observed in the open field test, novelty‐suppressed feeding test, sucrose preference test, forced swimming test, and tail suspension procedure. Results: We found that artesunate significantly prevented a H2 O2 ‐induced reduction in PC12 cell activity, suggesting its antioxidant potential. We also found that mice pretreated with artesunate (5, 15 mg/kg) intraperitoneally (i.p.) prior to the LPS (.8 mg/kg, i.p.) treatment showed fewer and less severe depression‐ and anxiety‐like behaviors than the LPS‐treated control mice. Conclusion: Our findings indicate that artesunate produces antioxidant effect, as well as antidepressant and anxiolytic effects. Importantly, our findings first demonstrate that artesunate can prevent LPS‐induced depression‐ and anxiety‐like symptoms, strongly suggesting its prophylactic potential in the treatment of depression and, perhaps, other psychiatric disorders associated with inflammation and oxidative stress. Abstract :